2
$\begingroup$

I'm looking at the following construction of the Hodge dual on Wikipedia: https://en.wikipedia.org/wiki/Hodge_dual

I'll summarize what Wikipedia says. We let $V$ be an $n$-dimensional vector space over the reals equipped with an inner product. We let $\{e_1,\dots,e_n\}$ be an orthogonal basis, and $\omega=e_1\wedge\cdots\wedge e_n$. The hodge dual by definition should be an $\Bbb R$-linear map $*:\Lambda^k(V)\to\Lambda^{n-k}(V)$ for any $0\le k\le n$ such that for all $\alpha,\beta\in \Lambda^k(V)$, $\alpha\wedge*\beta=(\alpha,\beta)\omega$.

Here is the construction:

If we fix $\lambda\in \Lambda^k(V)$, then for every $\theta\in \Lambda^{n-k}(V)$ there is a real number $f_{\lambda}(\theta)$ such that $\lambda\wedge\theta=f_{\lambda}(\theta)\omega$. This defines a bounded linear operator $f_{\lambda}:\Lambda^{n-k}(V)\to\Bbb R$, so by the Riesz representation theorem, there is an element $*\lambda\in \Lambda^{n-k}(V)$ such that $f_{\lambda}(\theta)=(\theta,*\lambda)$ for all $\theta$.

My question is, how does this give us what we need? I've checked that this is indeed $\Bbb R$-linear, but all the construction immediately gives us is $\lambda\wedge\theta=f_{\lambda}(\theta)\omega=(\theta,*\lambda)\omega$ for any $\lambda\in \Lambda^k(V)$, $\theta\in \Lambda^{n-k}(V)$.

How can I see that the desired relation holds for $\alpha,\beta\in \Lambda^k(V)$?

$\endgroup$
1
$\begingroup$

Let's not take my answer too seriously because I am not a specialist.

Due to switching between scalar products of each $\Lambda^k(V)$ and in order to not lose the sight on the compatibility between them, I prefer to construct $\star$, first, on orthonormal basis of $\Lambda^k(V)$ - by the definition of the scalar products on $\Lambda^k(V)$ inherited from the scalar product of $V$ - naturally associated to the orthonormal basis $\{e_1,\cdots,e_n\}$ of $\Lambda(V)=V$. Let us denote this orthonormal basis of $\Lambda^k(V)$ by $e_1^k,\cdots,e_{C_n^k}^k$.

Provided that $V$ is oriented, $\star$ is the only linear operator such that $e_i^k\wedge \star e_i^k = \omega$ for all $k=1,\cdots,n$ and $i=1,\cdots,C_n^k$ (the unicity is derived from the same argument you have used). Using the orthonormality and linearity we get that, $\alpha \wedge \beta = \{\alpha,\beta\}\omega$, where $\alpha = \sum \alpha_i e_i^k$, $\beta = \sum \beta_i e_i^k$ and $\{\alpha,\beta\} = \sum \alpha_i \beta_i$. Note that this definition is independent from the choice of the orthonormal basis

I think, If you breakdown your formalism into orthonormal basis, it will be easy to find your wanted formula. By the way, $\omega$ is chosen to be the volume form, i.e $(\omega,\omega)=1$. this is another reason why I think, using the decomposition in the orthonormal basis is the only way to show the formula.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.